Analysis of the Anticancer Phytochemicals in Andrographis paniculata Nees. under Salinity Stress. (28th November 2013) - Talei, Daryush; Valdiani, Alireza; Maziah, Mahmood; Sagineedu, Sreenivasa Rao; Saad, Mohd Said
Abstract : Salinity causes the adverse effects in all physiological processes of plants. The present study aimed to investigate the potential of salt stress to enhance the accumulation of the anticancer phytochemicals in Andrographis paniculata accessions. For this purpose, 70-day-old plants were grown in different salinity levels (0.18, 4, 8, 12, and 16 dSm −1 ) on sand medium. After inducing a period of 30-day salinity stress and before flowering, all plants were harvested and the data on morphological traits, proline content and the three anticancer phytochemicals, including andrographolide (AG), neoandrographolide (NAG), and 14-deoxy-11, 12-didehydroandrographolide (DDAG), were measured. The results indicated that salinity had a significant effect on the aforementioned three anticancer phytochemicals. In addition, the salt tolerance index (STI) was significantly decreased, while, except for DDAG, the content of proline, the AG, and NAG was significantly increased (P ≤ 0.01 ). Furthermore, it was revealed that significant differences among accessions could happen based on the total dry weight, STI, AG, and NAG. Finally, we noticed that the salinity at 12 dSm −1 led to the maximum increase in the quantities of AG, NAG, and DDAG. In other words, under salinity stress, the tolerant accessions were capable of accumulating the higher amounts of proline, AG, and NAG than the sensitive accessions.